Levels of Training and Development, Performance Management, and Job Satisfaction among Millennial Staff in the Provincial Government in Northern Luzon, Philippines - Charissa Marie E. Go (Philippine Social Science Journal, 2025)
This quantitative descriptive-correlational study examined how training, performance, and job satisfaction influence employee retention and whether these relationships vary by employment status. Data were collected from 348 respondents using a valid and reliable 64-item questionnaire, which was analyzed using descriptive statistics, Pearson correlation, and moderation analysis. The findings indicated that both regular and temporary staff perceive high levels of training, performance, and satisfaction. While training and performance consistently impacted retention across both groups, the moderation analysis revealed that employment status did not significantly alter the relationship between job satisfaction and retention. Consequently, future research should look beyond employment status and employ serial mediation analysis involving factors such as employer branding and engagement to gain comprehensive insights into talent management’s role in retention.